Mediator Subunit RhMED15a Regulates Drought Tolerance in Rose - Xiaoman Shang; Nanxin Xie; Yalin Li; Zixin Zhao; Ping Luo; Yongyi Cui; Xianlong Rao; Wen Chen (Horticulturae, 2024)
Mediator is a multiprotein complex integral to the transcription machinery, mediated by RNA polymerase II. Some Mediator subunits have been found to have critical functions in plants’ responses to abiotic stresses. However, the role of plant Mediator subunits in drought responses remains largely enigmatic. Here, we identified a Mediator subunit, RhMED15a, in roses (Rosa hybrida). Its expression was greatly and swiftly induced by dehydration treatment in the root. The promoter sequence of RhMED15a contains cis-acting elements that respond to abscisic acid (ABA) and methyl jasmonate (MeJA). In addition, the expression of RhMED15a was significantly up-regulated with ABA treatment and inversely down-regulated with MeJA treatment. Silencing RhMED15a using virus-induced gene silencing (VIGS) in roses significantly reduced drought tolerance in rose plants. This resulted in a significant increase in the malondialdehyde (MDA) level and a decreased survival rate in comparison to TRV controls. Moreover, we found that the expression of five drought-related genes, including dehydration responsive element binding factor 1B (DREB1B), responsive to desiccation stress 29A (RD29A), responsive to desiccation stress 29B (RD29B), early response to dehydration 14 (ERD14), and 9-cis-epoxycarotenoid dioxygenase 1 (NCED1), was considerably suppressed in RhMED15a-silenced plants during drought stress. Taken together, our results present that the Mediator tail module subunit RhMED15a serves as an enhancer of drought tolerance in rose, probably through the modulation of the expression of some drought-related genes.